DIFFUSIVE INSTABILITY AND SOME CRITICAL PARAMETERS RESULTING IN ITS OCCURRENCE - Zhavrin, Yu. I.; Kosov, V. N.; Asembaeva, M. K.; Poyarkov, I. V.; Fedorenko, O. V. (Recent Contributions to Physics, 2011)
The influence estimations of some parameters particularly temperature, diameter and length of a diffusion channel on the diffusion in ternary gas mixtures reducing to the onset of diffusion instability are given. Estimations were carried out by the two flask apparatus and were connected with the behavioral analyses of Rayleigh numbers, which permit to judge the boundary transition of mixing process from the molecular diffusion to the convection. In the result of study is shown what parameters make the mostcontribution to the formation of diffusive instability.
Keywords: the two flask apparatus; the molecular diffusion